The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1016/j.foodchem.2020.126922
|View full text |Cite
|
Sign up to set email alerts
|

In vitro oxidation promoted by chlorpyrifos residues on myosin and chicken breast proteins

Abstract: Organophosphate pesticides are frequently used to eliminate or prevent insects in poultry. However, their residues may continue in meat after slaughtering. In this study, proteomics and peptidomics approaches were used to evaluate their oxidative impact on myosin and chicken breast proteins under in vitro conditions. Myosin protein was exposed to diazinon and chlorpyrifos showing an increase in its oxidation by increasing times, especially with chlorpyrifos.Then, chicken breast was contaminated with chlorpyrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Although not included among the most affected pathways in the metabolome, the glutathione metabolism pathway was also identified in the metabolome of the high‐dose exposure to chlorpyrifos in Japanese quail. In addition, the decrease in proline could result from chlorpyrifos‐induced oxidative stress, as suggested by oxidation of the proline residue in chicken breast proteins after chlorpyrifos exposure (Márquez‐Lázaro et al, 2020). Our results are consistent with the literature on chlorpyrifos effects on oxidative stress across a range of species (Jeon et al, 2016; Narváez et al, 2016; Ojha et al, 2011; Olsvik et al, 2015; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although not included among the most affected pathways in the metabolome, the glutathione metabolism pathway was also identified in the metabolome of the high‐dose exposure to chlorpyrifos in Japanese quail. In addition, the decrease in proline could result from chlorpyrifos‐induced oxidative stress, as suggested by oxidation of the proline residue in chicken breast proteins after chlorpyrifos exposure (Márquez‐Lázaro et al, 2020). Our results are consistent with the literature on chlorpyrifos effects on oxidative stress across a range of species (Jeon et al, 2016; Narváez et al, 2016; Ojha et al, 2011; Olsvik et al, 2015; Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…13 Therefore, it would be expected that these types of changes can occur in chicken muscle proteins as well and influence the meat' nutritional value. 14 In conclusion, our results showed the oxidizing effect of tetracycline and β -lactam residues on chicken breast proteins, even at concentrations considered safe. This causes concern because carbonylation continues to occur even after the animal is slaughtered, which means that under in vivo conditions protein oxidation may be greater.…”
Section: Discussionmentioning
confidence: 53%
“…Then, samples were contaminated individually with 200 μL of each antibiotic working solutions until reaching final concentrations of 0.5, 1.0 and 1.5 MRL ( Table 1 ), followed by vortexing for 30s and then incubation for 1 h at room temperature in the dark. 14 All assays were carried out with three replicates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research found that a large number of peptides from collagen showed the oxidation of Pro residue after cooking and in vitro GI digestion of Spanish dry-cured ham (Gallego, Mora, Hayes, Reig & Toldrá, 2017). More recently, Pro residues from collagen were reported to be the main targets during in vitro oxidation of chicken breast (Márquez-Lázaro, Mora, Méndez-Cuadro, Rodríguez-Cavallo & Toldrá, 2020).…”
Section: Effect Of Cooking and Gastrointestinal Digestion On Peptide Profilementioning
confidence: 99%